Responsible Lending : Overview of Regulatory Tools - Prouza, Tomáš (World Bank, Washington, DC, 2014)
This paper provides an overview of key regulatory actions a government may implement to support responsible lending. It covers a range of possible interventions, including the provision of information, developing consumers' ability to use that information, formal requirements for responsible behavior of the lenders, and regulatory limits for loans. Because the research on the effectiveness of the responsible lending policies is limited, the paper focuses on literature overview and empirical evidence when available and uses case studies to describe key policies. A regulator seeking to develop a responsible lending framework must cover all areas of the responsible lending regulatory and educational mix. No single solution may be applied universally. The regulators must ensure they understand the retail credit markets. The paper identifies main policy options and areas for further research. Better data on lending markets before and after the rules are introduced and more detailed understanding of consumer behavior helps in identifying effective regulatory rules and supervisory actions that help ensure more responsible lending while not limiting financial inclusion and the growth of the credit market. Access to credit is sometimes considered by national authorities a crucial measure of financial inclusion. Low-income countries where microfinance is a key contributor financial inclusion may use similar measures.